MEASURING GUEST SATISFACTION AT BENDEGA RESTAURANT, AT RENON VILLAGE IN DENPASAR IN ASEAN ECONOMY COMMUNITY (AEC) ERA - I Ketut Sadia; I Nyoman Winia; I Ketut Redjasa (Institut Pariwisata dan Bisnis Internasional, 2016)
In Asean Economy Community (AEC) era, the competition in restaurant business is tighter and tighter, in domestic market or in international market (global market) . How to winning the competition?. The Bendega Restaurant must be able to offer an extremely good service to his guests, for example to offer outstanding service to all guests of Bendega restaurant, the price of food are so reasonable, quick service at all the times, much better service than the other competitors.Bad service, expensive food price, slow service, will make guest disappointed / dissatisfaction, although in a different degree.This research is aimed to know the activities of Bendega restaurant while measuring guest satisfaction at Bendega Restaurant at Renon Village in Denpasar in Asean Economy Community (AEC) era.Data of this research was collected by using direct observation, depth interview and documentation.The data are obtained from informants who know the object of research such as Restaurant Manager, Assistant Restaurant Manager, F&B Supervisor, Restaurant Captains and many waiters and waitress as the front liner of giving services in Bendega Restaurant.After that, the data was analyzed descriptively. One hundred questionairs were spreading out along one month on feb 2016. The result of the research showed that two third of guests were satisfied, a quarter of them were fair and the rest of them no respons with the services which were offered to the guests.According to the questionairs showed that the key of success by Bendega Restaurant was by offering fantastic services to their guests.